Někdy jsem rebelka, jindy slušná holka. Kulturní modely násilí z pohledu romských dívek - Trachtová, Zuzana (Romano džaniben, 2017)
The text is based on an ethnographic research of a  group of Romani teen youth in Prague. Within their peer communications, the teens often focused on the topic of violence. There are several similar teen Romani groups in Prague, which organize street fights amongst each other. Violence was a  dominant activity of the boys in teen groups. However, it was respected by girls from the group as well. This text presents a short survey into the girl´s view of the meaning of violence. As a theoretical framework for the data analysis, I selected the theory of cultural models. This method allows us to analyze the emic perspective of teens and to find out which metaphors are connected to violence, what violence means in their communication and what stands behind their decision to be or not to be a participant in the violence.
Keywords: violence; Roms; teenage groups; girls; gender differences; feminicity; masculinity; Prague